2016
DOI: 10.7314/apjcp.2016.17.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Active HCV infection amongst Blood Donors of Mardan District, Pakistan

Abstract: Hepatitis C is an ailment of liver caused by hepatitis C virus (HCV) infection. About 3% of the world population is infected by this virus. HCV infection is a leading reason for liver cirrhosis and therefore a major source of hepatocellular carcinoma. The study focused on the incidence of active HCV infection in blood donors of Mardan district of KPK, Pakistan. A total of 5318 blood donors were inspected for the presence of anti-HCV antibodies and HCV-RNA using ICT (immune-chromatographic test), ELISA and RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One of the key steps involved in triggering of apoptotic cascade is the leakage of cytochrome C from the mitochondria and subsequent activation of caspases [52]. Several studies reported that phytochemical compounds of M. oleifera were able to induce apoptosis in cancer cells [27, 53, 54]. In particular, moringin, the ITC resulting from myrosinase-catalysed hydrolysis of glucomoringin (GMG-ITC) was found to induce caspase 3-dependent apoptosis in multiple myeloma [28].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key steps involved in triggering of apoptotic cascade is the leakage of cytochrome C from the mitochondria and subsequent activation of caspases [52]. Several studies reported that phytochemical compounds of M. oleifera were able to induce apoptosis in cancer cells [27, 53, 54]. In particular, moringin, the ITC resulting from myrosinase-catalysed hydrolysis of glucomoringin (GMG-ITC) was found to induce caspase 3-dependent apoptosis in multiple myeloma [28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HCV varied among population. ELISA and RT-PCR techniques were used in many cities to determine the prevalence of HCV, including 6.6% in Kohat (11,12), 9.2% in the Swat Region, 5.2% in Mardan, 9.3% in DI Khan, and 12.9% in Abbottabad (12,13). The prevalence variations may be due to a variety of factors, including differences in the number of CKD patients in each study, genetic factors, immune status of patients, detection technique type, sample size, cultural knowledge of exposure to a risk factor for HCV transmission, and the diversity of the research that characterized the virus, which can contribute to a successful age group.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of HCV is not commonly high among individuals with antibodies, and this finding was unusual. There is no other mention to such a high prevalence of virus persistence [33,34]. …”
Section: Discussionmentioning
confidence: 99%